(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the master of the prophets and messengers, Muhammad and his good and pure family, and after:And when we are talking about the manifestations of revelation and the message of our Prophet Muhammad, may God’s prayers and peace be upon him, we must investigate the effects of that among the People of the Book among the Christians first, because they are the closest in affection to those who believe. The clear verses and conclusive evidence of the prophethood of the Messenger, may God’s prayers and peace be upon him, and how the nobles of the people stood against him with his violence when he offered them faith in Muhammad, peace be upon him, which is the credibility of His saying: ((And when they hear what was sent down to the Messenger, you see their eyes overflowing with tears because of what they knew of the truth)) (1)